HUBUNGAN KAUSALITAS PRODUK DOMESTIK BRUTO, IMPOR RIIL DAN IMPOR BARANG MODAL INDONESIA PERIODE 2000 –2016 DENGAN PENDEKATAN MODEL ANALISIS VECTOR AUTOREGRESSION (VAR) - Muhammad Gunawan Dwilaksono (Perpustakaan Universitas Surabaya, 2020)
The purpose of this study is to identify Causal Relationship of Gross Domestic Product, Real Import and Import of Capital Goods. The object used by this study is Indonesia with 17 years of time periods starting 2000 to 2016. This study used quantitative approach and time series method through Vector Autoregression model analysis. The result showed a causal relationship between its variables. Whilst the analysis of Variance Decomposition showed the contribution (percentage) of each variable which is still dominated by itself except the variable import of capital goods that is still dominated by imports of oil and gas and non-oil and gas. Based on impulse response analysis can be seen that the shock on the variable import of capital goods does not cause permanent effect while the import of raw materials of oil and gas and non-oil and gas have a permanent effect. The import relation on grossdomestic product shows indication of funding requirement as supporting import activity especially in oil and gas sector and non oil and gas sector.